An Analysis of Language Styles Used by Tour Guides in Huta Siallagan: A Study of International Tourist Satisfaction - Siburian, Sabrina Anjelina; Sihite, Jubilezer; Sembiring, Rony Arahta (ELT Worldwide: Journal of English Language Teaching, 2024)
This research delves into an examination of the language styles employed by tour guides in Huta Siallagan when interacting with international tourists. The primary objectives of this study were twofold: first, to categorize and identify the various types of language styles used by tour guides during their interactions with tourists, and second, to assess the overall satisfaction of international tourists with the services provided by these tour guides. To achieve these objectives, a descriptive qualitative method was employed. The research methodology followed the framework outlined by Miles and Huberman, encompassing data reduction, data display, and drawing conclusions from the collected information. The data collection process involved the transcription of voice recordings of tour guides and foreign tourists, which were then transformed into written scripts. Subsequently, these scripts were closely examined to identify specific linguistic elements, allowing for a detailed analysis of the language styles present in the tour guide-tourist interactions. For the analytical framework, Martin Joos' theory was utilized, providing a structured framework for understanding and categorizing the language styles used by tour guides. In total, the study analysed 77 utterances from the collected data. The findings of this research reveal that the most prevalent language style utilized by tour guides in Huta Siallagan when interacting with international tourists is the casual style. This outcome sheds light on the communicative preferences and practices of tour guides in this cultural and touristic context. These insights can be invaluable for tour operators, policymakers, and other stakeholders in the tourism industry, aiming to enhance the experiences of international tourists visiting Huta Siallagan.